Analisis Swot: Faktor Internal Dan Eksternal Pada Pengembangan Usaha Sayuran Hidroponik Di Kota Banda Aceh - Muhamad Ikhlasul Amal; Sofyan Sofyan; Zulkarnain Zulkarnain (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
The purpose of this research is to identify internal and external factors that influence the development of red sugar cane business. This study uses the method of evaluation of internal factors (IFE) and evaluation of external factors (EFE). Internal factor analysis is carried out to identify the company's internal strengths that can be used and anticipated weaknesses. External factor analysis is conducted to identify opportunities that can be exploited and threats that can be avoided. Based on the results of processing the IFE matrix, the total score generated is 3.58. While the total score for processing the EFE matrix is 3.14. Both scores are above 2.5 which means the internal position is quite strong. So that the company has an above average ability to take advantage of strengths and opportunities to anticipate weaknesses and threats. Its main strength lies in the location of the gardens that are close to consumers. While the weakness of the hydroponic vegetable business in Banda Aceh City is the lack of available exhibitions. The biggest opportunity is effective market segmentation. The threat faced is the increase in the price of raw materials.